Anatomy of Discourses: Body Politics in Andahazi’s The Anatomist - Seval, Ayşem (My University, 2017)
History of medicine seems to be a journey deep into the body and its diseases. This journey is not determined solely by disinterested scientific curiosity; it was and still is surrounded by a web of cultural, political, economic and religious agendas. Accordingly, the first part of the essay will map out the journey into the body and point out how the objectivity of scientific approaches that we today take for granted is a myth constructed around the eighteenth century, and how the medicalised body is never devoid of cultural baggage. With the aim to illustrate how the medical discourses depend on other discourses to perpetuate themselves as well as undermine the authority of those they depend upon, the second part of this essay will analyse Federico Andahazi’s The Anatomist, which employs a wide range of Renaissance discourses to parody religious, legal, scientific and sexual ‘grand narratives.’
Keywords: History of medicine; anatomy; Federico Andahazi; The Anatomist; Mateo Colombo